Abundance, Morphological Features, and Economic Values of Selected Tree Species in Company Graden of Saharanpur District, Uttar Pradesh, India - Simran Saini; Aleeza Usmani; Shifa Naaz; Swarna Pal Singh; Shaalu Sharma (AgroEnvironmental Sustainability)
This study aimed to assess the abundance, morphological features, and economic values of selected tree species (Mango, Eucalyptus, and Bottle brush) within Company Garden of Saharanpur, Uttar Pradesh, India. Through systematic survey and analysis, the results showed that Eucalyptus emerged as the most abundant species, constituting 40% of the tree population. Mango trees, comprising approximately 35% of the population, were out for their economic importance and cultural significance. While their cultivation offers economic benefits, their influence on biodiversity and soil health warrants careful evaluation, particularly in the context of human cultivation practices. Bottle brush trees, though least abundant at 15%, contribute uniquely to the ecosystem by providing ornamental value and potential wildlife habitat. Their ecological contributions emphasize the importance of preserving biodiversity within the ecosystem. On the other hand, analysis of morphological and economic features highlighted the distinct characteristics of each species. Eucalyptus, with its remarkable height and girth, proves valuable for timber production and ecological functions such as erosion control. Mango trees, prized for fruit production and shade provision, play a crucial role in agroforestry contexts. While Bottle brush trees may not be extensively utilized for timber, their ornamental value and ecological contributions are noteworthy. Overall, the study provides valuable insights into the abundance, morphological characteristics, and ecological significance of tree species within the Company Garden.